Effects of gestation and lactation on dry matter intake, dry matter digestibility, ruminal fermentation, and passage rates of primiparous beef heifers - Linden, Daniel R. (Kansas State University, 2011)
Two experiments were conducted to evaluate the effects of late gestation and early lactation on the nutritional status of beef heifers fed low-quality, warm-season grass hay. The first experiment compared DMI, DM digestibility, and ruminal dynamics of pregnant and lactating beef heifers to non-gestating, non-lactating heifers of a similar age and size. This study demonstrated that pregnant heifers ate less than non-pregnant heifers while maintaining similar digestibilities. Intake was similar between lactating and non-lactating, though DM digestibility increased postpartum in lactating heifers. Ruminoreticular fill was less for pregnant than for non-pregnant heifers; ruminoreticular fill was similar regardless of lactation status. Ruminal NH3 increased with increasing intakes throughout the study. Lactating heifers had less ruminal NH3 than non-lactating heifers. Total ruminal VFA concentration was similar from 10 wk prepartum through 10 wk postpartum except at 2 wk prepartum when gestating heifers had less total ruminal VFA concentration. The second experiment compared DMI, DM digestibility, passage rate, and plasma glucose and BHBA concentrations between pregnant heifers, pregnant cows, lactating heifers, and lactating cows which were fed low-quality, warm-season grass hay supplemented with 450 g/d of soybean meal. This study demonstrated that DMI increased with progressing gestation in heifers. Lactating heifers had greater intake than other groups postpartum. DM digestibility decreased with advancing gestation; gestating animals had greater digestibility than non-gestating animals. Lactation status did not influence DM digestibility, though lactating heifers had greater digestibility from 3 to 7 wk postpartum. Digestibility was not influenced by age. Pregnant animals had faster digesta passage rates than non-pregnant counterparts. Plasma glucose concentration increased during the prepartum period; pregnant and lactating animals had lesser plasma glucose concentrations than non-gestating, non-lactating animals. Plasma BHBA concentration was greater in pregnant and lactating animals than in non-pregnant and non-lactating animal; age was not an influence on BHBA concentration. Calves from mature cows grew faster than calves from heifers. These studies showed that beef heifers do not have the same patterns of intake as mature cows during late gestation. Heifers and their calves exhibited poorer performance when compared to mature cows when fed low-quality, warm-season grass hay.
Keywords: Beef heifer; Nutrition; Gestation; Lactation; Parturition; Animal Sciences (0475)